Adsorption of textile dyes on raw Tunisian clay: Equilibrium, kinetics and thermodynamics - Nahed, Naghmouchi; kais, nahdi (JOURNAL OF ADVANCES IN CHEMISTRY, 2015)
Natural clay from Nabeul region (north of Tunisia) was investigated for the removal of two anionic textile dyes (RR120 and BB150) from aqueous solution. The raw clay was characterized by means of XRD, IR spectroscopic, chemical analysis, cation exchange capacity and BET surface area analysis. Adsorption studies were carried out under various parameters such as pH, contact time, initial dye concentration and temperature. The adsorption kinetic data was tested by pseudo-first order, pseudo second-order and intra-particle diffusion kinetic models. The equilibrium data were analyzed using Langmuir, Freundlich, Temkin and Dubinin–Radushkevich isotherm models. The thermodynamic parameters (DH°, DS° and DG°) of the adsorption were also evaluated. The adsorption process was found spontaneous and endothermic in nature. The kinetics of adsorption were best described by pseudo-second order kinetic model. The Langmuir adsorption model totally agrees with the experimental data.